Monolayer Doping: A Shallow Acceptor of Phosphorous Doped in MoSe2 Monolayer (Adv. Electron. Mater. 1/2020). (13th January 2020) - Xia, Yipu; Zhang, Junqiu; Yu, Zhoubin; Jin, Yuanjun; Tian, Hao; Feng, Yue; Li, Bin; Ho, Wingkin; Liu, Chang; Xu, Hu; Jin, Chuanhong; Xie, Maohai
Abstract : Phosphorous doping in a MoSe2 monolayer is achieved by co‐deposition of P, Se, and Mo during molecular‐beam epitaxy, as reported by Maohai Xie and co‐workers in article number 1900830 . P atoms substitute Se in MoSe2, acting as acceptors and causing a Fermi‐level shift. The doping level can be tuned by changing the P/Se flux ratio. For dopants of the group‐V elements, the binding energy becomes shallower with increasing atomic mass.